Amino functionalization of graphene/graphene-like MoSe2 hybrids as lubricant additives for bismaleimide composites: Preparation, mechanical and tribological properties. (15th March 2019) - Chen, Zhengyan; Guo, Liulong; Yan, Hongxia; Yao, Huanhuan; Li, Lin; Liu, Qi
Abstract: Amine functionalization of graphene/graphene-like MoSe2 (NH2 -rGO/MoSe2 ) hybrid nanosheets were synthesized by a facile hydrothermal method. Then, as lubricant additives, the hybrids were doped into bismaleimide (BMI) matrix to reinforce the mechanical and tribological properties of BMI composites. Graphene-like MoSe2 was introduced into rGO to prevent re-stacking of the layers. The microstructure of NH2 -rGO/MoSe2 was also characterized. When the content of NH2 -rGO/MoSe2 was 0.6 wt.%, the composite could achieve the highest impact and flexural strengths of 19.3 kJ/m 2 and 167.2 MPa, respectively. For the 0.4 wt.% NH2 -rGO/MoSe2 /BMI composite, it reached the minimum values for coefficient of friction and volume wear rate of 0.22 and 2.03 × 10 −6 mm 3 /(N·m), decreased by 47.6% and 87.6% in comparison with those of pure BMI, respectively. The NH2 -rGO/MoSe2 hybrids, acting as solid lubricants, played a key role in the enhanced toughness of the composites and interfacial strength between BMI matrix and filler. Thus, the improved tribological properties of the NH2 -rGO/MoSe2 /BMI composites were obtained. Graphical abstract: Image 1 Highlights: NH2 -rGO/graphene-like MoSe2 hybrids were prepared by a hydrothermal method. Graphene-like MoSe2 was introduced into rGO to prevent re-stacking. BMI composites with various contents of nano-fillers had been fabricated. The 0.6 wt.% NH2 -rGO/MoSe2 /BMI composite had the maximum of mechanical strengths. The BMI composite with 0.4 wt.% filler exhibited the best tribological behavior.